2019
DOI: 10.1017/s1751731118002896
|View full text |Cite
|
Sign up to set email alerts
|

Robot milking and relationship with culling rate in dairy cows

Abstract: Cow routines and behavioral responses are altered substantially following the installation of robot milking. The present study was designed to analyze the effect that switching from milking parlor to automatic milking system (AMS) had on the culling rate (due to various causes) of dairy cattle. For this purpose, culling records and causes for culling were tracked in 23 dairy farms in the Galicia region (NW Spain). The animals in these farms were monitored for 5 years. For the present study, that length of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
1
10
0
3
Order By: Relevance
“…Three times per day milking and use of a custom heifer grower led to unfavourable trends in involuntary culling. Dairy farms in Spain that switched from conventional parlours to automated milking systems reported lower risk of death or emergency slaughter, but higher risk of culling due to low production, udder problems, infertility or lameness (Bugueiro et al, 2019). These higher risks are likely due to dairy farmers wanting to have mobile, easy to milk high-producing cows that do not need help in their automated milking systems.…”
Section: Productive Lifespan Of Dairy Cowsmentioning
confidence: 99%
“…Three times per day milking and use of a custom heifer grower led to unfavourable trends in involuntary culling. Dairy farms in Spain that switched from conventional parlours to automated milking systems reported lower risk of death or emergency slaughter, but higher risk of culling due to low production, udder problems, infertility or lameness (Bugueiro et al, 2019). These higher risks are likely due to dairy farmers wanting to have mobile, easy to milk high-producing cows that do not need help in their automated milking systems.…”
Section: Productive Lifespan Of Dairy Cowsmentioning
confidence: 99%
“…Before AMS introduction, average herd size was 88.5 cows, producing on average 9,178 kg/cow per year. Following AMS adoption, herd size, milk yield, and culling rate increased on average by 11.3 cows, 441 kg/cow per year, and 1.3%, respectively, and calving interval decreased by 7 d. Bugueiro et al (2019) reported similar results regarding the increase in milk yield and culling rate following AMS transition in Spanish herds. Number of cows per AMS unit averaged 54.4 cows, which is similar to that reported by Castro et al (2012) and less than the typically described AMS capacity of 60 milking cows (Rotz et al, 2003).…”
mentioning
confidence: 53%
“…As a result of this situation, the number of farms has been reduced [27] and this has given way to the intensification of farms in terms of size and production per animal [26,67]. In this scenario, new developments and technologies appeared to ease the work in the farms and to increase the productivity, as is the case of the AMS (Automatic Milking System) [68,69]. Besides, according to [57] in their studies, it has also brought about a clear tendency to the association of farms into cooperatives in order to be able to meet the demands of the market.…”
Section: Area Of Studymentioning
confidence: 99%